Effects of Formulation Variables and Storage Conditions on Light Protected Vitamin B12 Mixed Parenteral Formulations - Farnaz Monajjemzadeh; Fatemeh Ebrahimi; Parvin Zakeri-Milani; Hadi Valizadeh (Tabriz University of Medical Sciences, 2014)
Purpose: In this research the effect of vitamin B1 and B6 on cyanocobalamin stability in commercial light protected parenteral formulations and upon adding stabilizing agents will be investigated and best formulation composition and proper storage condition will be introduced. Methods: In this research some additives such as co solvents and tonicity adjusters, surfactants, antioxidants and chelating agents as well as buffer solutions, were used to improve the stability of the parenteral mixed formulations of B12 in the presence of other B vitamins (B1 and B6). Screening tests and accelerated stability tests were performed according to ICH guidelines Q1A (R2). Results: Shelf life evaluation revealed the best formulation and the proper storage condition. The results indicated the first kinetic models for all tested formulations and the optimum pH value was determined to be 5.8. There was no evidence of B12 loss when mixed with B1 and B6 in a medical syringe at room temperature for maximum of 8 hours. Conclusion: It is necessary to formulate vitamin B12 mixed parenteral solutions using proper phosphate buffers (pH=5.8) and to indicate "Store in refrigerator" on the mixed parenteral formulations of vitamin B12 with other B vitamins, which has not been expressed on the label of tested Brand formulations at the time of this study.